High-flame-retardant, high-thermal-conductivity and high-toughening epoxy resin packaging adhesive and preparation method thereof
The integration of a nitrogen-phosphorus-sulfur flame retardant, surface-modified graphene-boron nitride filler, and silicon oil toughener in epoxy resin encapsulants addresses performance conflicts, achieving high flame retardancy, thermal conductivity, and toughness, suitable for high-end electronic encapsulation.
Patent Information
- Application Number
- CN202510584473.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-07
- Publication Date
- 2025-07-15
AI Technical Summary
Existing epoxy resin packaging glues have performance shortcomings in flame retardancy, thermal conductivity and toughness, which is difficult to meet the needs of multi-performance synergistic improvement of high-end electronic packaging.
A self-developed nitrogen-containing phosphorus-sulfur flame retardant and surface-modified layered graphene composite boron nitride micropowder thermal filler, combined with phenyl modified silicone oil toughening agent, is used to prepare a high flame retardant, high thermal conductivity and high toughening epoxy resin packaging glue through collaborative design and process optimization.
It achieves high flame retardant performance (UL94 V-0 grade, LOI ≥30%), high thermal conductivity (≥5.3W/(m·K) and high toughness (elongation at break ≥5%), while reducing the negative impact of viscosity and mechanical properties, and complying with environmental protection requirements.
Smart Images

Figure BDA0005391295190000021 
Figure BDA0005391295190000051 
Figure BDA0005391295190000052
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of epoxy resin encapsulation adhesives, and particularly relates to a highly flame-retardant, highly thermally conductive, and highly toughened epoxy resin encapsulation adhesive and a preparation method thereof. Background Art
[0002] Due to its excellent bonding strength, chemical resistance, low shrinkage rate, and high insulation performance, epoxy resin has become the core material in the field of electronic packaging, occupying more than 90% of the market share. However, with the rapid development of electronic devices towards high frequency, high power, and miniaturization, the performance shortcomings of traditional epoxy resin encapsulation adhesives in terms of flame retardancy, thermal conductivity, and toughness are becoming increasingly prominent, making it difficult to meet the stringent requirements of new-generation semiconductor devices and extreme environment applications.
[0003] Currently, the following problems exist in epoxy resin encapsulation adhesives:
[0004] 1. Limitations in flame retardancy
[0005] The limiting oxygen index (LOI) of traditional epoxy resin is only 19 - 19.8%, belonging to flammable materials. Although halogen-free flame retardants have improved the flame retardancy efficiency through the synergistic effect of the condensed phase and the gas phase, their high addition amount will lead to a sharp increase in the viscosity of the system, deterioration of process performance, and a significant reduction in the mechanical strength of the material. In addition, halogen-containing flame retardants are restricted by the EU RoHS directive due to environmental toxicity, further promoting the R & D demand for halogen-free systems.
[0006] 2. Bottlenecks in thermal conductivity
[0007] The thermal conductivity of pure epoxy resin is only 0.2 W / (m·K), which is difficult to meet the heat dissipation requirements of high-power devices. Filled thermally conductive composites can improve the thermal conductivity by adding high-thermal-conductivity fillers such as alumina and diamond, but it is difficult to form a continuous thermal conduction path at low filling amounts, while high filling amounts (>60%) will lead to poor interfacial compatibility, increased brittleness of the material, and deterioration of processing fluidity.
[0008] 3. Technical contradictions in toughening modification
[0009] After curing, epoxy resin has a high crosslinking density and is brittle, and its elongation at break is usually less than 5%. Traditional toughening methods include blending with rubber elastomers or thermoplastic resins, but the rubber phase is likely to reduce the heat resistance, and the thermoplastic resin is difficult to be evenly dispersed due to its high melting point, resulting in fluctuations in mechanical properties.
[0010] Existing technologies mostly focus on improving single performance, while there are significant performance conflicts among flame retardancy, thermal conductivity, and toughness. For example, high filling of thermal conductive fillers will exacerbate interfacial stress concentration and reduce toughness; the introduction of flame retardants may damage the thermal conductive network structure. In addition, the encapsulation of wide-bandgap semiconductors requires materials to have both low coefficient of thermal expansion and resistance to high and low temperature cycling performance (-163 °C to 150 °C), further increasing the complexity of formulation design.
[0011] In summary, to develop an epoxy resin encapsulant with high flame retardancy (UL94 V-0 grade, LOI>30%), high thermal conductivity (>3 W / (m·K)), and high toughness (elongation at break>5%), it is urgent to achieve multi-performance balance through innovative material system design and process optimization to meet the technological iteration requirements of high-end electronic packaging. Summary of the Invention
[0012] To solve the above problems, the present invention proposes a high flame retardant, high thermal conductivity, and high toughness epoxy resin encapsulant and its preparation method. By adding a self-developed nitrogen, phosphorus, and sulfur-containing flame retardant to the epoxy resin system, experiments show that in the condensed phase, abundant carbon residues hinder the mass and heat exchange during combustion and also prevent combustible gases from being released into the combustion zone. In the gas phase, phosphorus and sulfur-containing free radicals can capture active free radicals (H* and OH*), which can end the combustion chain reaction, thus endowing the epoxy resin encapsulant with high flame retardant properties. The surface modifier modified layered graphene composite boron nitride micro-powder thermal conductive filler synergistically and efficiently enhances the "interface interaction" between the filler and the resin matrix, improves the compatibility and thermal conductivity between the two, and realizes the synergistic improvement of thermal conductivity and insulation. A phenyl-modified silicone oil toughening agent is added to the reaction system to ensure that the epoxy resin encapsulant has good toughness while having high flame retardancy and high thermal conductivity.
[0013] The technical solutions adopted are as follows:
[0014] A high flame retardant, high thermal conductivity, and high toughness epoxy resin encapsulant and its preparation method, the raw material components and their weight fraction ratios are:
[0015] 50-90 parts of epoxy resin;
[0016] 1-20 parts of nitrogen, phosphorus, and sulfur-containing flame retardant;
[0017] 1-20 parts of layered graphene composite boron nitride micro-powder thermal conductive filler;
[0018] 0.1-10 parts of toughening agent;
[0019] 0.1-20 parts of curing agent;
[0020] The raw material ratio should meet the following conditions: the addition ratio of the flame retardant, thermal conductive filler, and toughening agent is controlled at (1.0-8.0):(1.0-6.0):(0.1-4.0);
[0021] The molecular structure of the nitrogen-phosphorus-sulfur flame retardant is as follows:
[0022]
[0023] Wherein the range of n is between 10 and 100.
[0024] Furthermore, for the high flame-retardant, high thermal conductivity, and high toughening epoxy resin encapsulant, the size range of the layered graphene is between 20 - 50 nm, and the size range of the boron nitride micropowder is between 100 - 200 nm.
[0025] Furthermore, for the high flame-retardant, high thermal conductivity, and high toughening epoxy resin encapsulant, the nitrogen-phosphorus-sulfur flame retardant is synthesized through the following steps: (1) React 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO, 1.0 mol) with aniline (1.2 mol) and aminophenylethanone (1.15 mol) at 130 °C under argon protection, using p-toluenesulfonamide as a catalyst, and react for 8 - 12 hours to obtain the intermediate DOPO-NH2 with a yield of 88%; (2) React DOPO-NH2 with 4-(4-hydroxyphenylsulfonyl)phenyl acrylate (molar ratio 1:1.5) at 80 °C in an argon atmosphere for 6 hours, and obtain DOPO-NH-S through column chromatography purification with a yield of 93%.
[0026] Furthermore, for the high flame-retardant, high thermal conductivity, and high toughening epoxy resin encapsulant, the toughening agent is phenyl-modified silicone oil, which is obtained through the following steps: (1) Condense phenyl hydrolyzate and methyl cyclics under acidic conditions to generate methyl phenyl condensate. (2) Add the end-capping agent in stages, control the pH between 3 - 7, carry out equilibrium polymerization under negative pressure (-0.08 - 0.099 MPa), control the temperature at 100 - 180 °C, and the time at 2 - 5 hours. (3) Add silicon nitride to remove residual hydroxyl groups, then remove unreacted monomers by high-temperature degassing (200 - 400 °C), and adsorb and decolorize with activated carbon.
[0027] Furthermore, for the high flame-retardant, high thermal conductivity, and high toughening epoxy resin encapsulant, the epoxy resin is one or more of hydrogenated bisphenol A epoxy resin, hydrogenated bisphenol F epoxy resin, and phenolic epoxy resin.
[0028] Furthermore, for the nitrogen-phosphorus-sulfur flame retardant, after synthesis, it needs to be dried to constant weight in a vacuum oven (50 - 90 °C) and ground to a particle size less than 20 microns to improve dispersion.
[0029] Furthermore, for the high flame-retardant, high thermal conductivity, and high toughening epoxy resin encapsulation adhesive, the curing agent is one or more of boron trifluoride monoethylamine, methyltetrahydrophthalic anhydride, trimellitic anhydride, diaminodiphenyl sulfone, boron trifluoride-triethylenetetramine, and dicyandiamide / 2-methylimidazole.
[0030] The preparation method of the above-mentioned high flame-retardant, high thermal conductivity, and high toughening epoxy resin encapsulation adhesive comprises the following steps:
[0031] (1) Add epoxy resin, nitrogen, phosphorus, and sulfur-containing flame retardant, and toughening agent to a high-speed shear disperser according to a certain weight fraction for strong stirring, then add the modified thermal conductivity filler and continue stirring and mixing to obtain Component A;
[0032] (2) Add a curing agent to Component A obtained in step (1) and mechanically stir and mix evenly to obtain Component B;
[0033] (3) Pour Component B obtained in step (2) into a self-made mold, place it in a vacuum drying oven for degassing treatment, then raise the temperature for curing, and finally cool to room temperature to obtain the epoxy resin encapsulation adhesive material.
[0034] Furthermore, for the preparation method of the high flame-retardant, high thermal conductivity, and high toughening epoxy resin encapsulation adhesive, the modifiers for modifying the layered graphene composite boron nitride micro-powder thermal conductivity filler in step (1) include one or more of methyl methacrylate (PMMA), γ-glycidoxypropyltrimethoxysilane (KH560), γ-methacryloxypropyltrimethoxysilane (KH570), and bis(γ-triethoxysilylpropyl)tetrasulfide (CG-Si69).
[0035] Furthermore, for the preparation method of the high flame-retardant, high thermal conductivity, and high toughening epoxy resin encapsulation adhesive, the pouring speed is less than 5 ml / s, and stepwise curing is carried out: pre-curing at 10 - 30°C for 30 min → main curing at 50 - 100°C for 1 - 1.5 h → post-curing at 120 - 130°C for 30 min, and the stirring speed is 300 - 1200 rpm.
[0036] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0037] 1. The synergistic improvement of high flame-retardant performance and environmental protection
[0038] Using the self-developed nitrogen, phosphorus, and sulfur-containing flame retardant (DOPO-NH-S), through the synergistic mechanism of condensed-phase carbonization (residual carbon rate at 800°C > 25%) and gas-phase free radical quenching (capturing H* and OH*), UL94 V-0 level flame retardancy (LOI ≥ 30%) is achieved at a low addition amount (1 - 20 parts, total flame retardant ratio ≤ 15%), the smoke density is reduced by 40%, and it does not contain halogens, meeting the RoHS environmental protection requirements.
[0039] Compared with the traditional halogen-free flame retardants that require the addition of more than 30%, this solution significantly reduces the negative impact on the system viscosity and mechanical properties.
[0040] 2. Compatibility between high thermal conductivity and insulation
[0041] By surface-modifying graphene nanosheets (20 - 50 nm) and composite boron nitride micropowders (100 - 200 nm), a three-dimensional thermal conduction network is constructed, and the thermal conductivity is increased to 5.3 - 5.9 W / (m·K). The filler addition amount is only 1 - 20 parts. Through interface modification, the dispersibility is optimized to avoid the increase in brittleness and the deterioration of processing fluidity caused by high filling.
[0042] 3. Balance between high toughness and heat resistance
[0043] A phenyl-modified silicone oil toughening agent (0.1 - 10 parts) is introduced. Through the flexible silicon-oxygen chain segments, the stress is dispersed, and the elongation at break reaches 5.6 - 7.1% (traditional epoxy <5%), and the glass transition temperature (Tg) remains at 150 - 160 °C, with no significant decrease in heat resistance.
[0044] 4. Synergistic optimization of multiple properties and process friendliness
[0045] By adjusting the ratio of the flame retardant, thermal conductive filler, and toughening agent (1.0 - 8.0:1.0 - 6.0:0.1 - 4.0), the performance conflict among flame retardancy, thermal conductivity, and toughening in traditional technologies is broken through, and a comprehensive performance balance is achieved. The stepwise curing process (pre-curing → main curing → post-curing) combined with vacuum degassing reduces bubble defects, and the curing time is shortened by 30%.
[0046] 5. Environmental protection and cost advantages
[0047] The synthesis process of the flame retardant and toughening agent is efficient (yield 88 - 93%). The filler modification steps are simplified, reducing the raw material and energy consumption costs. The halogen-free flame retardant system and low-volatility formula conform to the trend of green manufacturing and meet the requirements of high-end fields such as new energy vehicles and 5G communication. Detailed implementation manners
[0048] In order to make the objectives, technical solutions, and advantages of the present invention more clearly understood, the present invention will be further described in detail below in conjunction with examples and comparative examples.
[0049] In the following examples and comparative examples, the epoxy resin is purchased from Anhui Xinyuan Technology Co., Ltd., graphene, boron nitride, and curing agent are all purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., and the toughening agent is purchased from Shenzhen Masni Elastomer Co., Ltd. For those not specified in the examples, they are carried out under conventional conditions or the conditions recommended by the manufacturer. For those reagents or instruments without indicating the manufacturer, they are all conventional products that can be obtained through commercial purchase.
[0050] Example 1
[0051] A preparation method of a high flame - retardant, high thermal - conductivity and high toughening epoxy resin encapsulation adhesive, the raw material components and their weight - fraction ratios are as follows:
[0052] 80 parts of epoxy resin;
[0053] 10 parts of nitrogen - phosphorus - sulfur - containing flame retardant;
[0054] 6 parts of layered graphene - composite boron nitride micropowder thermal - conductivity filler;
[0055] 2 parts of toughening agent;
[0056] 2 parts of curing agent;
[0057] Among them, the addition ratio of the flame retardant, the thermal - conductivity filler and the toughening agent is 5:3:1;
[0058] The molecular structure of the nitrogen - phosphorus - sulfur - containing flame retardant is as follows:
[0059]
[0060] Among them, the value of n is 25 ± 5.
[0061] The epoxy resin is hydrogenated bisphenol A - type epoxy resin E51, the curing agent is methyltetrahydrophthalic anhydride, and the modifier for modifying the layered graphene - composite boron nitride micropowder thermal - conductivity filler is γ - glycidoxypropyltrimethoxysilane (KH560).
[0062] The pouring speed is 3 ml / s, and step - by - step curing is carried out: pre - curing at 20℃ for 30 min → main - curing at 100℃ for 1.5 h → post - curing at 130℃ for 30 min, and the stirring speed is 1000 rpm.
[0063] Example 2
[0064] A preparation method of a high flame - retardant, high thermal - conductivity and high toughening epoxy resin encapsulation adhesive, the raw material components and their weight - fraction ratios are as follows:
[0065] 80 parts of epoxy resin;
[0066] 14 parts of nitrogen - phosphorus - sulfur - containing flame retardant;
[0067] 2 parts of layered graphene - composite boron nitride micropowder thermal - conductivity filler;
[0068] 2 parts of toughening agent;
[0069] 2 parts of curing agent;
[0070] Among them, the addition ratio of the flame retardant, the thermal - conductivity filler and the toughening agent is 7:1:1;
[0071] The molecular structure of the nitrogen - phosphorus - sulfur - containing flame retardant is as follows:
[0072]
[0073] Among them, the value of n is 25 ± 5.
[0074] The epoxy resin is hydrogenated bisphenol A type epoxy resin E51, the curing agent is methyltetrahydrophthalic anhydride, and the modifier for modifying the layered graphene composite boron nitride micropowder thermal conductive filler is γ-glycidoxypropyltrimethoxysilane (KH560).
[0075] The pouring speed is 3 ml / s, step curing is carried out: 20°C / 30 min pre-curing → 100°C / 1.5 h main curing → 130°C / 30 min post-curing, and the stirring speed is 1000 rpm.
[0076] Example 3
[0077] A preparation method of a high-flame-retardant, high-thermal-conductivity and high-toughness epoxy resin encapsulant, the raw material components and their weight fraction ratios are as follows:
[0078] 80 parts of epoxy resin;
[0079] 2 parts of nitrogen, phosphorus and sulfur-containing flame retardant;
[0080] 12 parts of layered graphene composite boron nitride micropowder thermal conductive filler;
[0081] 4 parts of toughening agent;
[0082] 2 parts of curing agent;
[0083] Among them, the addition ratio of the flame retardant, the thermal conductive filler and the toughening agent is 1:6:2;
[0084] The molecular structure of the nitrogen, phosphorus and sulfur-containing flame retardant is as follows:
[0085]
[0086] Among them, the value of n is 25 ± 5.
[0087] The epoxy resin is hydrogenated bisphenol A type epoxy resin E51, the curing agent is methyltetrahydrophthalic anhydride, and the modifier for modifying the layered graphene composite boron nitride micropowder thermal conductive filler is γ-glycidoxypropyltrimethoxysilane (KH560).
[0088] The pouring speed is 3 ml / s, step curing is carried out: 20°C / 30 min pre-curing → 100°C / 1.5 h main curing → 130°C / 30 min post-curing, and the stirring speed is 1000 rpm.
[0089] Example 4
[0090] A preparation method of a high flame-retardant, high thermal conductivity, and high toughening epoxy resin encapsulation adhesive, with the raw material components and weight fraction ratios as follows:
[0091] 86 parts of epoxy resin;
[0092] 2 parts of nitrogen, phosphorus, and sulfur-containing flame retardant;
[0093] 2 parts of layered graphene composite boron nitride micropowder thermal conductive filler;
[0094] 8 parts of toughening agent;
[0095] 2 parts of curing agent;
[0096] Among them, the addition ratio of the flame retardant, thermal conductive filler, and toughening agent is 1:1:4;
[0097] The molecular structure of the nitrogen, phosphorus, and sulfur-containing flame retardant is as follows:
[0098]
[0099] Among them, the value of n is 25 ± 5.
[0100] The epoxy resin is hydrogenated bisphenol A type epoxy resin E51, the curing agent is methyltetrahydrophthalic anhydride, and the modifier for modifying the layered graphene composite boron nitride micropowder thermal conductive filler is γ-glycidoxypropyltrimethoxysilane (KH560).
[0101] The pouring speed is 3 ml / s, and stepwise curing is carried out: pre-curing at 20°C for 30 min → main curing at 100°C for 1.5 h → post-curing at 130°C for 30 min, and the stirring speed is 1000 rpm.
[0102] Control Example 1
[0103] The difference from Example 1 is that no nitrogen, phosphorus, and sulfur-containing flame retardant is added, and the others are the same as in Example 1.
[0104] Control Example 2
[0105] The difference from Example 1 is that no modified layered graphene composite boron nitride differential thermal conductive filler is added, and the others are the same as in Example 1.
[0106] Control Example 3
[0107] The difference from Example 1 is that no toughening agent is added, and the others are the same as in Example 1.
[0108] Control Example 4
[0109] The difference from Example 1 is that no nitrogen, phosphorus, and sulfur-containing flame retardant, no modified layered graphene composite boron nitride differential thermal conductive filler, and no toughening agent are added, and the others are the same as in Example 1.
[0110] Thermal conductivity test: The thermal conductivity of the encapsulant is tested according to ASTM D5470 standard;
[0111] Flame retardancy test: The vertical burning test meets the test requirements of V-0 level according to UL-94 standard on the CZF-2 type vertical burning tester. The limiting oxygen index is tested by HC-2 type oxygen index meter according to GB / T 2406-2008.
[0112] Mechanical property test: Tensile strength and elongation at break are tested by a tensile testing machine according to the method of GB / T 528-2009, and the tensile rate is set at 200mm / 0min.
[0113]
[0114]
[0115] From the above various examples, comparative examples and the corresponding performance test analysis tables, it can be seen that by comparing the performance data of the examples and the control examples, the following key conclusions can be drawn:
[0116] 1. Improvement of flame retardancy
[0117] Examples 1-4: Using self-developed nitrogen-phosphorus-sulfur flame retardant (DOPO-NH-S), the limiting oxygen index (LOI) reaches 30.2-36.1%, UL94 V-0 level, and the smoke density is reduced by 40%.
[0118] Control example 1 (without flame retardant): LOI is only 21.3%, UL94 V-1 level, indicating that the flame retardant plays a decisive role in the flame retardancy efficiency. Control example 4 (without flame retardant / filler / toughening agent): LOI is as low as 19.8%, UL94 V-2 level, and the comprehensive performance is the worst.
[0119] 2. Improvement of thermal conductivity
[0120] Example 1: The thermal conductivity is 5.9W / (m·K), which is 29 times higher than that of pure epoxy resin (0.2W / (m·K)), attributed to the three-dimensional thermal conduction network of modified layered graphene / boron nitride filler.
[0121] Control example 2 (without thermal conductive filler): The thermal conductivity is only 3.1W / (m·K), indicating that the filler contributes significantly to the thermal conductivity.
[0122] 3. Significantly enhanced toughness
[0123] Example 1: The elongation at break is 7.1% (traditional epoxy <5%), benefiting from the flexible chain segments of phenyl-modified silicone oil to disperse stress. Control example 3 (without toughening agent): The elongation at break drops to 3.4%, verifying the key role of the toughening agent.
[0124] 4. Multi-performance Synergistic Effect
[0125] Example 1: When the ratio of the flame retardant, thermal conductive filler, and toughening agent is 5:3:1, a synergistic optimization of the thermal conductivity of 5.9 W / (m·K), LOI of 36.1%, and elongation at break of 7.1% is achieved.
[0126] Comparative Example 4: When the key components are not added, the comprehensive performance deteriorates comprehensively, highlighting the necessity of component synergy.
[0127] In summary, for the high-flame-retardant, high-thermal-conductivity, and high-toughening epoxy resin encapsulation adhesive and its preparation method of the present invention, through the synergistic design and process optimization of the flame retardant-thermal conductive filler-toughening agent, it is significantly superior to the prior art in terms of flame retardancy, thermal conductivity, toughness, and process adaptability, providing a solution to the industry problem of multi-performance synergistic improvement of electronic encapsulation adhesives and having broad application prospects.
[0128] The above embodiments only represent several implementation manners of the present invention, but should not be construed as limiting the scope of the present invention patent. It should be noted that for those of ordinary skill in the art, without departing from the concept of the present invention, several modifications and improvements can still be made, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention patent shall be subject to the appended claims.
[0129] The above are only the embodiments and comparative examples of the present invention, and are not used to limit the present invention. Any modifications, equivalent replacements, and improvements made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A high flame-retardant, high thermal conductivity, and high toughening epoxy resin encapsulation adhesive and its preparation method, characterized in that The raw material components and their weight fraction ratios are as follows: 50 - 90 parts of epoxy resin; 1 - 20 parts of nitrogen, phosphorus, and sulfur-containing flame retardant; 1 - 20 parts of layered graphene composite boron nitride micropowder thermal conductive filler; 0.1 - 10 parts of toughening agent; 0.1 - 20 parts of curing agent; The raw material ratio should meet the following conditions: the addition ratios of the flame retardant, thermal conductive filler, and toughening agent are controlled within (1.0 - 8.0):(1.0 - 6.0):(0.1 - 4.0); The molecular structure of the nitrogen, phosphorus, and sulfur-containing flame retardant is as follows: Where the range of n is between 10 and 100.
2. The high-flame-retardant, high-thermal-conductivity, and high-toughness epoxy resin encapsulating adhesive according to claim 1, wherein The size range of the layered graphene is between 20 - 50 nm, and the size range of the boron nitride micropowder is between 100 - 200 nm.
3. The high flame-retardant, high thermal conductivity, and high toughening epoxy resin encapsulation adhesive according to claim 1, wherein, The nitrogen, phosphorus, and sulfur-containing flame retardant is synthesized through the following steps: (1) React 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) with aniline and aminoacetophenone at 130 °C under argon protection and p-toluenesulfonamide as a catalyst for 8 - 12 hours to obtain the intermediate DOPO-NH2 with a yield of 88%; (2) React DOPO-NH2 with 4-(4-hydroxyphenylsulfonyl)phenyl acrylate (molar ratio 1:1.5) at 80 °C under an argon atmosphere for 6 hours, and purify it by column chromatography to obtain DOPO-NH-S with a yield of 93%; The molar ratio of the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), aniline (1.2 mol), and aminoacetophenone is: 1.0:1.2:1.15。 4. The high-flame-retardant, high-thermal-conductivity, and high-toughness epoxy resin encapsulation adhesive according to claim 1, characterized in that The toughening agent is phenyl-modified silicone oil and is obtained through the following steps: (1) Condense phenyl hydrolyzate with methyl cyclics under acidic conditions to generate methyl phenyl condensate; (2) Add the end-capping agent in stages, control the pH between 3 - 7, carry out equilibrium polymerization under negative pressure (-0.08 - 0.099 MPa), control the temperature at 100 - 180 °C, and the time at 2 - 5 hours; (3) Add silicon nitride to remove residual hydroxyl groups, then remove unreacted monomers by high-temperature degassing (200 - 400 °C), and adsorb and decolorize with activated carbon.
5. The high-flame-retardant, high-thermal-conductivity, and high-toughness epoxy encapsulation adhesive according to claim 1, wherein The epoxy resin is one or more of hydrogenated bisphenol A epoxy resin, hydrogenated bisphenol F epoxy resin, and phenolic epoxy resin.
6. The nitrogen-phosphorus-sulfur flame retardant according to claim 3, wherein After synthesis, it needs to be dried to constant weight in a vacuum oven and ground to a particle size less than 20 microns to improve dispersibility.
7. The high-flame-retardant, high-thermal-conductivity, and high-toughness epoxy encapsulating adhesive according to claim 1, wherein, The curing agent is one or several of boron trifluoride monoethylamine, methyltetrahydrophthalic anhydride, trimellitic anhydride, diaminodiphenyl sulfone, boron trifluoride-triethylenetetramine, and dicyandiamide / 2-methylimidazole.
8. The preparation method of the high flame-retardant, high thermal conductivity and high toughening type epoxy resin encapsulating adhesive according to any one of claims 1-7, characterized in that It includes the following steps: (1) Add epoxy resin, nitrogen, phosphorus, and sulfur-containing flame retardant, and toughening agent according to a certain weight fraction to a high-speed shear disperser for strong stirring, then add the modified thermal conductive filler and continue stirring and mixing to obtain Component A; (2) Add the curing agent to Component A obtained in step (1) and mechanically stir and mix evenly to obtain Component B; (3) Pour Component B obtained in step (2) into a self-made mold, place it in a vacuum drying oven for degassing treatment, then heat up for curing, and finally cool to room temperature to obtain the epoxy resin encapsulation adhesive material.
9. The preparation method of the high flame-retardant, high thermal conductivity and high toughness epoxy resin encapsulating adhesive according to claim 8, characterized in that, The modifier for modifying the layered graphene composite boron nitride micro-powder thermal conductive filler in the step (1) includes one or more of methyl methacrylate (PMMA), γ-glycidoxypropyltrimethoxysilane (KH560), γ-methacryloxypropyltrimethoxysilane (KH570), and bis(γ-triethoxysilylpropyl)tetrasulfide (CG-Si69).
10. The preparation method of the high flame-retardant, high thermal conductivity and high toughness-increasing epoxy resin encapsulating adhesive according to claim 8, wherein, The pouring speed is less than 5 ml / s, and stepwise curing is carried out: pre-curing at 10 - 30 °C for 30 min → main curing at 50 - 100 °C for 1 - 1.5 h → post-curing at 120 - 130 °C for 30 min, and the stirring speed is 300 - 1200 rpm.
Citation Information
Cited By
Toughened modified epoxy resin material and preparation method thereof
CN120923973A
Flame-retardant battery cell lead terminal sealant and preparation method thereof
CN121379470A
Cooling fin and preparation method and application thereof
CN121495304A